Citrullination negatively regulates the functions of the p53 protein and opposes its ubiquitination and degradation - Yi-Fang Yang; Chien-Yun Lee; Guang-Yaw Liu; Ju-yi Hsieh; Yi-Chun Lin; Li-Wei Wang; Kai-Han Chan; Won-Shin Yen; Yin-Chu Chen; Chi-Li Lin; Hui-chih Hung (Proceedings of the National Academy of Sciences, 2025)
This study investigates the regulatory role of peptidylarginine deiminase 4 (PAD4)-mediated citrullination on the tumor suppressor protein p53. We demonstrate that p53 serves as a substrate for PAD4, undergoing citrullination at multiple arginine residues, including critical sites within its DNA-binding domain. Mass spectrometry identified eight citrullination sites, notably R158, R282, and R283, which were further validated in various cancer cell lines. Functional studies revealed that citrullination significantly impairs p53’s ability to form stable tetramers, essential for high-affinity DNA binding. Electrophoretic mobility shift assays and analytical ultracentrifugation confirmed reduced binding to consensus sequences in the p21 and MDM2 promoters. As a result, citrullination led to marked reductions in p21 and MDM2 transcriptional activation and altered regulation of ME2, as demonstrated by reporter assays and quantitative PCR. In addition, citrullination compromised p53’s roles in cell cycle control and apoptosis. Supporting these findings, citrulline-mimic mutants (arginine-to-glutamine substitutions) exhibited diminished transcriptional activity relative to wild-type p53. Furthermore, citrullination disrupted the interaction between p53 and its E3 ubiquitin ligase MDM2, reducing p53 ubiquitination and degradation, as shown by in vitro ubiquitination assays and cycloheximide chase experiments. Importantly, replacing glutamine with lysine at these key sites largely restored p53 activity, indicating that the loss of positive charge is central to the functional consequences of citrullination. Together, these findings identify PAD4-catalyzed citrullination as a regulatory mechanism that modulates p53 function and highlight PAD4 as a potential therapeutic target in cancer.